Manisfestation of Ecological Consciousness in Early Arabic Literature: A Comparative Ecocriticism Approach between The Pre-Islamic and The Early Islamic Period - Saepul Anwar; Lukman Sumarna; Rismawati (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2026)
This study examines the manifestations of ecological consciousness in Arabic literature during the Pre-Islamic (Jāhiliyyah) and Early Islamic periods, focusing on the continuities and transformations in representations of the human–nature relationship. Using a comparative descriptive-analytical approach within the framework of ecocriticism, the research analyzes selected poetic texts through library-based study of relevant primary and secondary sources. The findings show that ecological consciousness in Pre-Islamic poetry was closely connected to the realities of desert life and survival. Natural elements such as deserts, mountains, rain, water, and animals were depicted as integral to human existence, cultural identity, and collective memory. In Early Islamic poetry, these ecological elements underwent a significant reinterpretation under the influence of the Islamic worldview of tawḥīd. Nature was no longer viewed solely as a physical environment but also as a manifestation of divine signs that reveal God’s power, wisdom, and providence. Consequently, elements such as water, mountains, the sky, light, and dawn acquired spiritual and ethical meanings that emphasized the interconnected relationship between humans, nature, and the Creator. The study concludes that Arabic poetry evolved from an adaptive-existential ecological consciousness in the Pre-Islamic era to a theo-ecological consciousness in the Early Islamic period while preserving a profound sensitivity to the natural environment.